OpenStack service function chaining interface - Car, Mario (2015)
OpenStack is a free and open-source cloud computing software platform. It is seen as a major technology enabler for the future of telecommunications. OpenStack eases the creation of virtualization environments, and is seen as a major technology for the development of network function virtualization (NFV). Currently, OpenStack is developing the use cases and the code for service function virtualization, but the higher layer management aspects are not being considered. This dissertation will address this challenge, and will work on the creation of an interface for a simple usage of the NFV functions, enabling the network manager to build services by concatenation of graphical elements. The Application Programming Interfaces that are currently being developed will be analyzed and a simple web interface to explore theirs potentialities will be created.